Assessment of hemodialysis patients’ response to Erythropoietin - العبد الله, ربا; إبراهيم سليمان ,; فراس حسين, (Latakia University Journal -Medical Sciences Series, 2023)
Introduction: Anemia is a common complication in hemodialysis patients and its presence is associated with a reduced quality of life, increases mortality rates, and its treatment constitutes an economic burden. Research Methods: A prospective study was conducted that included 112 hemodialysis patients at Tishreen University Hospital in Lattakia, during the period from October 2021 to March 2022. Erythropoietin was administered to each patient with a hemoglobin value ≤11.5 g/dl in initial doses. 20-50 units/kg*3 weekly, then the dose was later adjusted according to the hemoglobin values ​​that were monitored monthly, but not to exceed 300 units/kg weekly. The type of erythropoietin used was subcutaneous alpha and beta. Results: The number of patients who responded to the treatment was 35 patients. By comparing the characteristics of the responding patients with the non-responders, we noticed that there was no significant difference in the demographic characteristics or the cause of renal insufficiency, and that URR% was statistically significant by 5% higher within the responders group, and for the values ​​of both Ferritin, calcium and PTH were statistically significant after 6 months, and there was a close relationship between high ERI values, high PLR values, and non-response to treatment. A significant decrease in dependence on blood transfusion occurred. All patients with severe anemia. We reached the maximum dose of erythropoietin in 84 patients out of 112, of whom only 17 patients achieved a response at the end of the study from those treated with the maximum dose, while 8 patients reached the target hemoglobin without reaching the target. for the maximum dose of erythropoietin. Conclusions: Ferritin, PTH, Ca and the adequacy of dialysis played a role in the response to erythropoietin, and there was a significance of the ERI and the ratio of platelets to lymphocytes in predicting non-response, while increasing the dose of erythropoietin did not increase the chances of improving hemoglobin values ​​in our study.